The use of wearable technology to measure and support abilities, disabilities and functional skills in autistic youth: a scoping review. - Black, Melissa; Milbourn, Benjamin; Chen, Nigel TM; McGarry, Sarah; Wali, Fatema; Ho, Armilda SV; Lee, Mika; Bolte, Sven; Falkmer, Torbjorn; Girdler, Sonya (2020)
Background: Wearable technology (WT) to measure and support social and non-social functioning in Autism Spectrum Disorder (ASD) has been a growing interest of researchers over the past decade. There is however limited understanding of the WTs currently available for autistic individuals, and how they measure functioning in this population.